THE INFLUENCE OF PRICE PERCEPTION AND PRODUCT ATTRIBUTES ON CONSUMER PURCHASE DECISION OF SECOND-HAND CLOTHES IN SOUTH MINAHASA - Angelina Laurina Paat; Frederik G. Worang; Emilia M. ` Gunawan (Universitas Sam Ratulangi, 2023)
The secondhand clothing trend also appears to be driven by affordability, especially now, during the pandemic COVID-19 economic crisis. Even though now the pandemic has changed status to endemic, the trend of fashion business development in South Minahasa is growing rapidly, not only in new fashion, but also imported secondhand fashion. The successful of the second-hand clothes industry caused by the consumer purchase decision of the product. In seeing a price, consumers have some different thoughts. Prices that have been determined are above competitors' prices, it can be seen that the quality of the goods is getting better and the prices of goods are very expensive. Meanwhile, Product attributes are the factors considered by the buyer at the time of purchasing the product, such as price, quality, completeness function (features), design, after-sales service and others. The purpose of this study is to know the simultaneous and partial influence of price perception and product attributes on consumer purchase decision of secondhand clothes in South Minahasa This research used multiple regression analysis with sample of 90 respondents. The result shows price perception and product attributes have a simultaneous and partial influence on consumer purchase decision of second-hand clothes. Based on the result, all the seller should keep their price suitable with the market price and affordable for the consumer and also should choose a good supplier of the second-hand clothes and also choose a premium pack of clothes. Keywords: price perception, product attributes, consumer purchase decision